2021
DOI: 10.1101/2021.05.26.445846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular electron transfer increases fermentation in lactic acid bacteria via a hybrid metabolism

Abstract: Energy conservation in microorganisms is classically categorized into respiration and fermentation, however recent work shows some species can use mixed or alternative bioenergetic strategies. We explored the utility of a flavin-based extracellular electron transport (FLEET) system for energy conservation within diverse lactic acid bacteria (LAB), microorganisms that mainly rely on fermentative metabolism and are important in food fermentations. The LAB Lactiplantibacillus plantarum uses extracellular electron… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 114 publications
0
27
0
Order By: Relevance
“…Dynamic binding between eDNA and electron shuttles in oxidized or reduced states accelerates electron exchange. During food fermentation, some LAB, including Lactiplantibacillus plantarum , were found to use a hybrid strategy to conserve energy, in that the LAB used extracellular electron transfer to increase the NAD+/NADH ratio and then generated more ATP through substrate‐level phosphorylation (Tejedor‐Sanz et al., 2022). This suggested a regulatory approach using extracellular electron transfer to modulate the microbial biomass, metabolic flux, product yield, and flavor profiles of fermented foods.…”
Section: Microbial Interactions In Multispecies Biofilmsmentioning
confidence: 99%
“…Dynamic binding between eDNA and electron shuttles in oxidized or reduced states accelerates electron exchange. During food fermentation, some LAB, including Lactiplantibacillus plantarum , were found to use a hybrid strategy to conserve energy, in that the LAB used extracellular electron transfer to increase the NAD+/NADH ratio and then generated more ATP through substrate‐level phosphorylation (Tejedor‐Sanz et al., 2022). This suggested a regulatory approach using extracellular electron transfer to modulate the microbial biomass, metabolic flux, product yield, and flavor profiles of fermented foods.…”
Section: Microbial Interactions In Multispecies Biofilmsmentioning
confidence: 99%
“…This allowed us and others to identify other Gram-positive microbes capable of EET, including Enterococcus faecalis and Lactiplantibacillus plantarum . 5,79 At present, however, it is not understood how exclusively fermentative microbes, such as L. plantarum and E. faecalis , can utilize and maintain an EET pathway, especially when a traditional respiratory system is not maintained. Elucidating this phenomenon and its influence on organismal physiology is of great importance due to the prevalence of these Gram-positive bacteria in agriculture, bioremediation, food production, gut health, and opportunistic human infections.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that the genus Lactiplantibacillus has a highly conserved FLEET locus and many of its members exhibit EET activity. 9 The FLEET locus encodes a type-II NADH dehydrogenase (Ndh2), flavin transport proteins (FmnA/B and ATPase1/2), membrane demethylmenaquinone (DMK) synthesis proteins (DmkA and EetB/DmkB), and electron transfer proteins (PplA and EetA). 79 An exogenous menaquinone (MK) precursor, 1,4-dihydroxy-2-naphthoate (DHNA), was added to allow the microbe to synthesize MK or DMK.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations